(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
A novel inhibitor, 1-[(4-methylphenyl)Sulfonyl]-4â€“pyridine-2-ylpiperazine (MSPP)Â has beenÂ synthesized and characterized using FT-IR, 1H NMR,13C NMR , LC-MSÂ and UV-visibleÂ spectroscopy methods.TheÂ inhibitive effect of 1-[(4-methylphenyl)sulfonyl]-4-pyridin-2-ylpiperazine(MSPP) on the corrosion of mild steel in 1M HCl was investigated by weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. The efficiency of the inhibitor increases with the increase in the inhibitor concentration and decrease with a rise in temperature. Potentiodynamic polarization study showed that the inhibitor acts as mixed type. EIS finding showed that the change in the impedance parameters (Rct and Cdl), with the variation in MSPP concentration is due to the adsorption of active molecules leading to the formation of protective layer on the surface of mild steel. The UV-visible absorption spectra indicate the formation of a MSPP-Fe complex. The adsorption data fitted with Langmuir adsorption isotherm. Thermodynamic parameters such as activation energy (Ea), free energy change (Î”Gads ), enthalpy change (Î”Hads ) and entropy change (Î”Sads ) wereÂ also evaluated and discussed in detail. Surface analysis by AFM and SEM confirmed the formation of protective coating on the mild steel surface. Quantum chemical calculation were also performed using density functional theory.